Comparing the Characteristics of Amniotic Membrane-, Endometrium-, and Urinary-Derived ECMs and Their Effects on Endometrial Regeneration in a Rat Uterine Injury Model - Ji, Wanqing; Wen, Jiaming; Lin, Weige; He, Ping; Hou, Bo; Quan, Song (Frontiers in Bioengineering and Biotechnology, 2022)
The decellularized extracellular matrices (d-ECMs) currently utilized to repair endometrial injuries are derived from three tissue sources, the endometrium (dE-ECM), placental amniotic membrane (dA-ECM), and urinary (dU-ECM). Notably, the structures of dU-ECM and dE-ECM are similar. These d-ECMs are derived from different tissues, and their specific roles in endometrial injury repair remain unclear. This study aimed to analyse the characteristics of the tissue microstructures and compositions to confirm specific differences among the three ECM types. And using a rat model of endometrial injury, the effects of all the matrices after implantation in vivo on the promotion of endometrial regeneration were analysed. After decellularization, dE-ECM had more residual active factors than the other two ECM types, while dA-ECM had significantly less DNA, α-Gal antigen components and extracellular matrix components than the other two groups. Although the three ECMs had no effect on the proliferation of stromal cells in vitro, dA-ECM may have increased the sensitivity of stromal cells to oestradiol (E2) responses. In vivo experiments confirmed the promotional effect of dA-ECM on endometrial regeneration. For example, the endometrial thickness, collagen deposition, endometrial tissue regeneration, vascular regeneration and pregnancy outcomes were significantly better in this group than in the other two groups. These findings might be associated with the excellent immune tolerance of dA-ECM. Therefore, when selecting a d-ECM for the treatment of endometrial injury, dE-ECM, which has the strongest tissue specificity, is not the preferred choice. Controlling the inflammatory responses in local lesions at the early stage may be a prerequisite for ECMs to exert their functions.